One Health surveillance: linking human and animal rabies surveillance data in Kenya - Kahariri, Samuel; Thomas, Lian F.; Bett, Bernard K.; Mureithi, M.; Njuguna, B.; Mutono, N.; Mwangi, T. (Frontiers Media, 2025)
Introduction: Rabies poses a significant public health and economic challenge in Kenya. The Kenya rabies elimination strategy identifies surveillance as a key pillar to achieve the targets of ending human deaths from rabies by 2030. Here we investigated the utility of the national human and animal rabies surveillance data to provide robust surveillance data to guide the Kenya rabies elimination program.